Pengembangan Strategi Komunikasi Yang Efektif Pada Badan Pengawas Pemilihan Umum Provinsi Jawa Barat - Hermawan, Herry (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Election is not only an indicator of democracy, but also an important part of democracy. In implementing this democratic process, the election supervisory institution (Badan Pengawas Pemilihan Umum - Bawaslu) develops a communication strategy as a preventive effort against potential violations in the election. So, the role of Bawaslu is to design messages to persuade and motivate the public so they activelyparticipate to create clear and clean election. The aim of this program is, for participants, to understand effective communication strategies and to have effective communication skills. The participants were members of the Public Relations Division of Bawaslu in the area of West Java, totaling 40 people. The program was carried out from 17 November 2022 up to 18 November 2022 in Bogor City, and 15 December 2022 in Bandung District. The development of an effective communication strategy is carried out using lecture, practice and question and answer methods. Overall, these activities, both public relations development and writing press releases training, can be said to be successful. The benefit is they can know, understand and apply better communication techniques and these qualities can be used as points in assessing the quality of Bawaslu.